UNDESCENDED CAECUM AND APPENDIX WITH RIGHT SIDED SIGMOID COLON - A CASE REPORT - Jacob, Meera; H., Shivarama C.; S., Bindu; Nallathamby, Rani; R., Avadhani (Journal of Health and Allied Sciences NU, 2013)
During routine dissection of abdomen for undergraduate students in Yenepoya Medical College, a male cadaver presented with variation in disposition of large intestine and inferior mesenteric artery. Caecum and appendix were present in the right lumbar region. The descending colon crossed the median plane in front of great vessels to the right side and then it continued as sigmoid colon in the right iliac fossa. Inferior mesenteric artery arose from right side of abdominal aorta to supply the left one third of ascending colon, descending colon and sigmoid colon.
Keywords: Descending colon; Sigmoid colon; Inferior mesenteric artery